2017
DOI: 10.1080/08927014.2017.1319473
|View full text |Cite
|
Sign up to set email alerts
|

Surface sensing and stress-signalling inUlvaand fouling diatoms – potential targets for antifouling: a review

Abstract: Understanding the underlying signalling pathways that enable fouling algae to sense and respond to surfaces is essential in the design of environmentally friendly coatings. Both the green alga Ulva and diverse diatoms are important ecologically and economically as they are persistent biofoulers. Ulva spores exhibit rapid secretion, allowing them to adhere quickly and permanently to a ship, whilst diatoms secrete an abundance of extracellular polymeric substances (EPS), which are highly adaptable to different e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 228 publications
(248 reference statements)
0
8
0
Order By: Relevance
“…Incubation experiments of plastic substrates in the marine environment have demonstrated that the physiochemical characteristic of the substratum surface (such as hydrophobicity, surface texture, and chemical nature) can affect colonizing communities [16,32,[39][40][41][42], and surface hydrophobicity has been considered as a factor affecting microbial cell adhesion because microbes attach more rapidly to hydrophobic surfaces than hydrophilic surfaces [15,43,44]. Previous research reported that diatom genera (such as Achnanthes, Amphora, Cocconeis, Navicula, and Synedra) adhered more strongly to hydrophobic surfaces, inhibiting motility and release, than hydrophilic surfaces, where diatom gametes swarming and release was enhanced [45]. With respect to the substrate types used in our study, PE is the most hydrophobic (water contact angle, θ = 101.7°), followed by PP (θ = 99°), PS (θ = 87°), and glass (θ = 51°) in descending order with lower water contact values indicating more hydrophilic surfaces [16].…”
Section: Substrate-driven Biofilm Structuresmentioning
confidence: 99%
“…Incubation experiments of plastic substrates in the marine environment have demonstrated that the physiochemical characteristic of the substratum surface (such as hydrophobicity, surface texture, and chemical nature) can affect colonizing communities [16,32,[39][40][41][42], and surface hydrophobicity has been considered as a factor affecting microbial cell adhesion because microbes attach more rapidly to hydrophobic surfaces than hydrophilic surfaces [15,43,44]. Previous research reported that diatom genera (such as Achnanthes, Amphora, Cocconeis, Navicula, and Synedra) adhered more strongly to hydrophobic surfaces, inhibiting motility and release, than hydrophilic surfaces, where diatom gametes swarming and release was enhanced [45]. With respect to the substrate types used in our study, PE is the most hydrophobic (water contact angle, θ = 101.7°), followed by PP (θ = 99°), PS (θ = 87°), and glass (θ = 51°) in descending order with lower water contact values indicating more hydrophilic surfaces [16].…”
Section: Substrate-driven Biofilm Structuresmentioning
confidence: 99%
“…The model diatom P . tricornutum , a planktonic species that also has a benthic morphotype (i.e., oval cell form), usually appears as fusiform in liquid cultures under non-stress conditions, and it contributes to biofilm formation and biofouling upon morphology shift and surface colonization ( Thompson and Coates, 2017 ). The cell and molecular biology of biofouling are largely unknown, even though environment-friendly antifouling coatings are urgently needed.…”
Section: Discussionmentioning
confidence: 99%
“…Diatoms have evolved intricate signaling pathways in response to environmental fluctuations, allowing them to be the dominant clade of microalgae in oceans ( Thompson and Coates, 2017 ). Among the signaling pathways in cell differentiation and morphogenesis ( Basson, 2012 ), G-protein-coupled receptor (GPCR) signaling pathway is highly conserved across eukaryotes and plays an essential role in signal transduction and response to extracellular stimuli ( Chan et al., 2015 ; Cohen et al., 2017 ; Port et al., 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…The use of anti-adhesive polymer thin-film coatings for biomedical implants represents a strategy of reducing, or ideally eliminating, susceptibility to bacterial infections while maintaining desired material properties. , Surface properties that have been shown to influence bacterial adhesion include roughness, hydrophobicity, and charge. To this end, efforts have been made to reduce bacterial adhesion through modification of surface abrasion, in addition to surface coating and grafting. , Zwitterionic polymers, which maintain electrical neutrality with equivalent positive and negative charged groups, have also been identified as ultra-low fouling materials that effectively prevent bacterial adhesion. , Prior work has described that these zwitterionic polymers attract and order water molecules that maximize hydrogen bonding. These strong interactions between the zwitterion and water are significant to disrupt, thereby largely preventing other species, such as biomolecules to adhere .…”
Section: Introductionmentioning
confidence: 99%